Crohn’s disease complicated with a bladder-fistula – a case report - Pasternak, Grzegorz; Bartusik-Aebisher, Dorota; Aebisher, David; Filip, Rafał (European Journal of Clinical and Experimental Medicine, 2021)
<p style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction. Entero-bladder fistula (fistula entero-vesicalis) is a pathological connection between the lumen of the gastrointestinal tract and the bladder. Entero-bladder fistulas are not a common condition. The main reason for the formation of entero-bladder fistulas are intestinal diseases occurring within the intestinal loop adjacent to the bladder resulting in the formation of an abnormal channel, the connection between the above structures <p style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Aim. The aim is to present the causes of the fistulas can be divided into congenital and acquired (intestinal infection, cancer, Crohn’s disease, resulting from trauma and iatrogenic). Clinical manifestations of the biliary-bullous fistulae may be from the digestive or urinary tract. The most characteristic ailments are pneumaturia, fecuria, urge to urinate, frequent urination, lower abdominal pain, hematuria, urinary tract infection. <p style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Description of the case. The article discusses the case of a patient with Leśniowski-Crohn disease complicated with a bladder-fistula. The treatment of entero-bladder fistulas is primarily surgical, it consists in resection of the fistula together with resection of the affected intestine and bladder wall fragment. <p style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. The test confirming the presence of an entero-bladder fistula is a test with oral administration of poppies, although it happens that the test result may be negative, especially in the case of a bladder-follicular fistula. Among the tests useful in the diagnosis of entero-bladder fistula include abdominal ultrasound, computed tomography, magnetic resonance imaging, endoscopic tests (colonoscopy or cystoscopy).